Pengaruh Pembelajaran Multimedia Interaktif Bagi Mahasiswa - Atika Sari br pa; Lili Saputri; Muhammad Faiz; Ali Ikhwan (CV. ITTC INDONESIA, 2022)
The learning process is a deliberate effort by educators to impart knowledge, and create environmental systems using various methods so that students can complete learning activities effectively and efficiently and achieve optimal results. Multimedia is media that combines two or more elements consisting of text, graphics, images, photos, audio and animation in an integrated manner. Apart from making it easier for students to understand what they want to convey and so that the message can convey its meaning clearly, multimedia has the ability to stimulate the senses and allows humans to adjust to their own learning pace. This interactive learning can help users learn on their own. In addition, users are more interested in learning because of the attractive sound design and features. The purpose of this study is to determine the influence and development of multimedia learning media for students.